Minería, instituciones y sostenibilidad: desencuentros y desafíos - Bebbington, Anthony J. (2010)
Global consumption continues to generate growth in mining. In lesserdeveloped economies, this growth offers the potential to generate newresources for development, but also creates challenges to sustainabilityin the regions in which extraction occurs. This context leads todebate on the institutional arrangements most likely to build synergiesbetween mining, livelihoods, and development, and on the socio-politicalconditions under which such institutions can emerge. Buildingfrom a multiyear, three country program of research projects, Peru, aglobal center of mining expansion, serves as an exemplar for analyzingthe effects of extractive industry on livelihoods and the conditionsunder which arrangements favoring local sustainability might emerge.This program is guided by three emergent hypotheses in human environmentalsciences regarding the relationships among institutions,knowledge, learning, and sustainability. The research combines indepthand comparative case study analysis, and uses mapping andspatial analysis, surveys, in-depth interviews, participant observation,and our own direct participation in public debates on the regulation ofmining for development. The findings demonstrate the pressures thatmining expansion has placed on water resources, livelihood assets,and social relationships. These pressures are a result of institutionalconditions that separate the governance of mineral expansion, waterresources, and local development, and of relationships of power thatprioritize large scale investment over livelihood and environment. Afurther problem is the poor communication between mining sectorknowledge systems and those of local populations. These results areconsistent with themes recently elaborated in sustainability science.